Gender-based screening for chlamydial infection and divergent infection trends in men and women. - Susan M Rogers; Charles F Turner; William C Miller; Emily Erbelding; Elizabeth Eggleston; Sylvia Tan; Anthony Roman; Marcia Hobbs; James Chromy; Ravikiran Muvva; Laxminarayana Ganapathi (PLoS ONE)
Objectives To assess the potential impact of chlamydial screening policy that recommends routine screening of women but not men. Methods Population surveys of probability samples of Baltimore adults aged 18 to 35 years in 1997-1998 and 2006-2009 collected biospecimens to estimate trends in undiagnosed chlamydial infection. Survey estimates are compared to surveillance data on diagnosed chlamydial infections reported to the Health Department. Results Prevalence of undiagnosed chlamydial infection among men increased from 1.6% to 4.0%, but it declined from 4.3% to 3.1% among women (p = 0.028 for test of interaction). The annual (average) number of diagnosed infections was substantially higher among women than men in both time periods and increased among both men and women. Undiagnosed infection prevalence was substantially higher among black than non-black adults (4.0% vs 1.2%, p = 0.042 in 1997-98 and 5.5% vs 0.7%, p<0.001 in 2006-09). Conclusion Divergent trends in undiagnosed chlamydial infection by gender parallel divergent screening recommendations that encourage chlamydial testing for women but not for men.